Diabetes Mellitus Is Associated With Reduced High-Density Lipoprotein Sphingosine-1-Phosphate Content and Impaired High-Density Lipoprotein Cardiac Cell Protection. Issue 5 (May 2016) - Brinck, Jonas W.; Thomas, Aurélien; Lauer, Estelle; Jornayvaz, François R.; Brulhart-Meynet, Marie-Claude; Prost, Jean-Christophe; Pataky, Zoltan; Löfgren, Patrik; Hoffstedt, Johan; Eriksson, Mats; Pramfalk, Camilla; Morel, Sandrine; et al.
Abstract : Objective—: The dyslipidemia of type 2 diabetes mellitus has multiple etiologies and impairs lipoprotein functionality, thereby increasing risk for cardiovascular disease. High-density lipoproteins (HDLs) have several beneficial effects, notably protecting the heart from myocardial ischemia. We hypothesized that glycation of HDL could compromise this cardioprotective effect. Approach and Results—: We used in vitro (cardiomyocytes) and ex vivo (whole heart) models subjected to oxidative stress together with HDL isolated from diabetic patients and nondiabetic HDL glycated in vitro (methylglyoxal). Diabetic and in vitro glycated HDL were less effective ( P <0.05) than control HDL in protecting from oxidative stress. Protection was significantly, inversely correlated with the degree of in vitro glycation ( P <0.001) and the levels of hemoglobin A1c in diabetic patients ( P <0.007). The ability to activate protective, intracellular survival pathways involving Akt, Stat3, and Erk1/2 was significantly reduced ( P <0.05) using glycated HDL. Glycation reduced the sphingosine-1-phosphate (S1P) content of HDL, whereas the S1P concentrations of diabetic HDL were inversely correlated with hemoglobin A1c ( P <0.005). The S1P contents of in vitro glycated and diabetic HDL were significantly, positively correlated (both <0.01) with cardiomyocyte survival during oxidative stress. Adding S1P to diabetic HDL increased its S1P content and restored its cardioprotective function. Conclusions—: Our data demonstrate that glycation can reduce the S1P content of HDL, leading to increased cardiomyocyte cell death because of less effective activation of intracellular survival pathways. It has important implications for the functionality of HDL in diabetes mellitus because HDL-S1P has several beneficial effects on the vasculature. Abstract : Supplemental Digital Content is available in the text.